Robot Pointer sebagai Penunjuk Jalan Tim SAR untuk Mempermudah Pencarian Korban Bencana Gempa - Syadza Sausan; Bima Sakti; Hendrik Leo; Achmi Yuliani; Intan Permatasari; Aulia Rahman; Mohd Syaryadhi (Universitas Syiah Kuala, 2017)
An earthquake is a natural disaster caused by the movement of the earth plates or from below the Earth surface. The impact of the earthquake could lead casualties and other losses whether material or immaterial. The evacuation process of the victims must immediately proceed. The SAR (Search and Rescue) team has a duty to rescue victims who trapped in the rubble of the building. But information about the position of the victims could not be known precisely, and the environment around the location of the disaster is still very dangerous that might endanger the safety of SAR Team. In this research, a robot path pointer was designed to help SAR team in locating the victims. The method used in this research is the robot wirelessly controlled by SAR team at SAR team’s post with remote control. The robot searches in the rubble of the building and sends the victim’s location information to SAR team. This robot pointer research aims to find safe routes for SAR team of the victim’s location to reduce the risks that may harm the SAR team. The robot will give the main results of the pointer in the form of location coordinates and routes of the victim so that the SAR team only have to follow the route. Robot pointer guides the SAR team to the location of the earthquake in a short and less risky path for victim evacuation.